Lohengrin : Romantic opera in three acts - WAGNER, Richard (Breitkopf & Hartel)
King henry, Frederick, ortrud, the herald, saxon and thuringian nobles, brabantine noblesnThe same, elsa and ladies attendantnthe same, lohengrinnetc.